PREVAILING CONDITIONS OF REGIONAL COOPERATION OF THE FERGANA VALLEY REGIONS (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article discusses about the current level of interregional economic cooperation of Fergana, Namangan and Adijan (Fergana valley) provinces of Uzbekistan. The purpose of the study is to analyze and give recommendations based on the existing issues on interregional socio-economic cooperation, the level of interdependence, innovation and technologies for business people and government officers of the country.